QUICK FREEZING OF FRUITS AND VEGETABLES AND THEIR SUBSEQUENT STORAGE GOLD DRIED FRUITS EXPROT (Academicia Globe: Inderscience Research, 2022)
Freezing is the process of lowering the temperature of a product below the cryoscopic (freezing point) until most of the water contained in the product crystallizes. The crystallization process consists of two phases, including the nucleation of crystals and their growth. As the temperature decreases, the kinetic energy of water molecules decreases, and crystallization centers begin to form. The nucleation of crystals occurs when a group of water molecules is ordered and this structure is preserved, followed by its enlargement due to the involvement of new water molecules.